A systematic review exploring the impact of focal leader behaviours on health care team performance. (29th July 2021) - O'Donovan, Róisín; Rogers, Lisa; Khurshid, Zuneera; De Brún, Aoife; Nicholson, Emma; O'Shea, Marie; Ward, Marie; McAuliffe, Eilish
Abstract: Aim: The aim of this study is to understand how the behaviour of focal leaders impacts health care team performance and effectiveness. Background: Despite recent shifts towards more collectivistic leadership approaches, hierarchical structures that emphasize the role of an individual focal leader (i.e., the formal appointed leader) are still the norm in health care. Our understanding of the effect of focal leader behaviours on health care team performance remains unclear. Evaluation: A systematic review was conducted. Five electronic databases were searched using key terms. One thousand forty‐seven records were retrieved. Data extraction, quality appraisal and narrative synthesis were conducted in line with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Key issues: Fifty papers met the criteria for inclusion, were reviewed and synthesized under the following categories: task‐focused leadership, directive leadership, empowering leadership and relational focused leadership . Conclusions: Categories are discussed in relation to team performance outcomes, safety specific outcomes, individual‐level outcomes and outcomes related to interpersonal dynamics. Emerging themes are explored to examine and reflect on how leadership is enacted in health care, to catalogue best practices and to cascade these leadership practices broadly. Implications for Nursing Management: Empowering and relational leadership styles were associated with positive outcomes for nursing team performance. This underscores the importance of training and encouraging nursing leaders to engage in more collaborative leadership behaviours.